2021
DOI: 10.1016/j.neurol.2021.01.005
|View full text |Cite
|
Sign up to set email alerts
|

No impact of confinement during COVID-19 pandemic on anxiety and depression in Parkinsonian patients

Abstract: Background: Governments around the world have imposed varied containment measures to curb the spread of the COVID-19 infection. The psychological impact could be highly negative in patients with neurologic condition like Parkinson’s Disease (PD). Methods: We prospectively evaluated symptoms of depression and anxiety in 50 (26 females ; mean age at 60.4) non demented Moroccan PD patients, using Hospital Anxiety and Depression Scale (HADS), at the beginning and after 6 weeks of a full confinement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 7 publications
1
30
1
3
Order By: Relevance
“…Conversely, our data showing similar levels on the HADS questionnaire in both cohorts could be surprising, since several studies conducted even in heathy subjects showed how the COVID-19 pandemic significantly increased the levels of stress and anxiety [36][37][38]. On the other hand, two studies evaluating patients with chronic diseases (Parkinson's disease [39] and multiple sclerosis [40]) are in line with our findings, showing how the COVID-19 pandemic did not significantly increase the HADS scores. Probably, the attitude to living in contact with hospitals and other patients with different diseases reduced the fear and the anxiety of developing new pathologies, such as COVID.…”
Section: Discussionsupporting
confidence: 78%
“…Conversely, our data showing similar levels on the HADS questionnaire in both cohorts could be surprising, since several studies conducted even in heathy subjects showed how the COVID-19 pandemic significantly increased the levels of stress and anxiety [36][37][38]. On the other hand, two studies evaluating patients with chronic diseases (Parkinson's disease [39] and multiple sclerosis [40]) are in line with our findings, showing how the COVID-19 pandemic did not significantly increase the HADS scores. Probably, the attitude to living in contact with hospitals and other patients with different diseases reduced the fear and the anxiety of developing new pathologies, such as COVID.…”
Section: Discussionsupporting
confidence: 78%
“…Global and regional studies from America (US, Canada, Brazil), Asia (China, Japan, South Korea, India, Iran Israel, Turkey), North Africa (Egypt), or European countries (Luxembourg, Netherlands, UK, Italy, Spain, Slovenia) reported wide-ranging consequences of the pandemic on PwP, such as worsened motor and non-motor symptoms [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], a negative impact on mental health [ 29 ], a decline in quality of life [ 20 , 21 , 30 ], disrupted social and medical activities [ 12 , 13 ], impaired access to PD medication [ 21 , 31 , 32 ], or other unmet needs such as emotional distress, problems with rescheduling appointments with health care providers, and reduction in physical activity [ 2 , 14 , 20 , 22 , 24 , 33 , 34 ]. On the other side, although hours of caregiving at home and caregiver burden increased [ 33 ], patients and caregivers seem to be well informed and to have coped well in some studies [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of this study is the lack of measurement of anxiety and depression in study I. Such a study was conducted by Otomani et al They found no general differences in anxiety and depression after 6 weeks of isolation due to COVID-19 [22]. These authors also found no association of age, gender, and functional limitations associated with PD with both anxiety and depression.…”
Section: Discussionmentioning
confidence: 79%